2017
DOI: 10.1039/c7tc04300g
|View full text |Cite
|
Sign up to set email alerts
|

Two dimensional hexagonal boron nitride (2D-hBN): synthesis, properties and applications

Abstract: Comprehensive summary of the progress including crystal structures, fabrication methods, applications (especially for electronics) and functionalization of 2D-hBN from its discovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
605
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 864 publications
(617 citation statements)
references
References 280 publications
11
605
0
1
Order By: Relevance
“…[134] As an indirect band-gap semiconductor, h-BN exhibits unique electronic properties with a low dielectric constant, high thermal conductivity, and chemical inertness. Similar to graphene, the different h-BN planes are dominated by weak van der Waals interactions, while the in-plane nitrogen and boron atoms are combined by sp 2 orbitals to form strong σ-bonds, which are highly polarized because of the high asymmetry of the sublattices, resulting in the large band gap (5-6 eV) of h-BN.…”
Section: Hybrids Of C 60 and Hexagonal Boron Nitridementioning
confidence: 99%
“…[134] As an indirect band-gap semiconductor, h-BN exhibits unique electronic properties with a low dielectric constant, high thermal conductivity, and chemical inertness. Similar to graphene, the different h-BN planes are dominated by weak van der Waals interactions, while the in-plane nitrogen and boron atoms are combined by sp 2 orbitals to form strong σ-bonds, which are highly polarized because of the high asymmetry of the sublattices, resulting in the large band gap (5-6 eV) of h-BN.…”
Section: Hybrids Of C 60 and Hexagonal Boron Nitridementioning
confidence: 99%
“…Tw o-dimensional (2D) materials have attracted much attention since the rediscovery of graphene,a2D allotrope of carbon. [1] Since then, various 2D materials have been studied, for example,hexagonal boron nitride, [2] which is isoelectronic with graphene;silicene [3] and germanene, [4] which are heavier graphene analogues;a nd ah uge family of transition-metal dichalcogenides [5] (MoS 2 ,WS 2 ,etc) and MXenes, [6] which are layered transition-metal carbides and/or nitrides.The possible applications are mainly direct consequence of alarge surface area the 2D material and its conductivity;therefore,the main focus is towards electrochemical applications, [7] sensors, [8] supercapacitors, [9] and batteries. [10] Although many 2D materials have already been prepared, tested, and show excellent properties,new electronic devices require ac ertain size of band gap,w hich cannot be satisfied with these materials.T herefore,the search for materials that could overcome these limits has started.…”
Section: Introductionmentioning
confidence: 99%
“…Besides these, theoretical analysis reveals a band gap of 6.0 eV. This difference in band gap is due to electronic band dispersion caused by layer-to-layer interaction (Zhang et al 2017b;Kumbhakar et al 2015). Upon incorporation of Zr, red shift in wavelength was observed that serves to decrease band gap from 5.72 to 4.55 eV as demonstrated in Fig.…”
Section: Resultsmentioning
confidence: 86%